Naqd-i suḵẖan : yaʻnī, Bāqiyāt-i Fānī par Navvāb ʻAzīz Yār Jang Bahādur ʻAzīz kī suḵẖanvarānah tanqīd - ʻAzīz, ʻAzīz Yār Jang, b. 1873 or 4. (SAMP early 20th-century Indian books project, 1938)
On the poetry of Fānī Badāyūnī, 1870-1942, Urdu poet.